2008
DOI: 10.1007/s11095-008-9725-x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic Evaluation of Oral Estradiol Nanoparticles in Estrogen Deficient (Ovariectomized) High-Fat Diet Induced Hyperlipidemic Rat Model

Abstract: Together, these results demonstrate the ability of nanoparticles in improving oral bioavailability/efficacy of estradiol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…We also monitored the physiological parameters during surgery such as heart rate, respiratory rate and blood pressure. Ovariectomy was performed as described previously (Mittal et al ., ). Female rats were then randomly divided into six groups and were fed on respective diets for model development (Figure ).…”
Section: Methodsmentioning
confidence: 97%
“…We also monitored the physiological parameters during surgery such as heart rate, respiratory rate and blood pressure. Ovariectomy was performed as described previously (Mittal et al ., ). Female rats were then randomly divided into six groups and were fed on respective diets for model development (Figure ).…”
Section: Methodsmentioning
confidence: 97%
“…Additionally, following oral administration, E2 PLGA formulations of varying molecular weight (14,500, 45,000 and 213,000 Da) and varying lactide to glycolide ratios (50:50, 65:35) each showed detectable levels of E2 5–11 days after administration, which was significantly longer compared to the dose matched free E2 oral delivery, with detectable levels seen for only 1 day after administration 58 . In a high-fat induced hyperlipidemic rat model, E2 PLGA treatment administered orally every 3 days for 2 weeks significantly reduced body weight compared to controls, whereas a daily oral administration of an E2 suspension did not have a significant effect on body weight 56 . On the other hand, the E2 PLGA treatment in an AD model was effective at preventing amyloid beta plaque formation, but no significant benefit was seen between orally administered E2 PLGA versus E2 suspension treatment 55 .…”
Section: E2 Delivery Using Plga Mncsmentioning
confidence: 85%
“…E2 PLGA MNCs have been studied most commonly in the context of oral or transdermal administration. For instance, Dr. Kumar’s laboratory has analyzed the pharmacokinetics of E2 PLGA following oral administration as well as the effects of E2 PLGA oral treatment in a high-fat induced hyperlipidemic rat model and in an AD rat model 55,56,57,58 . Following 100 ug/kg E2 oral administration, they showed that E2 PLGA treatment resulted in a maximum E2 plasma level of 85 pg/ml at 24 hours, whereas E2 suspension resulted in a maximum E2 plasma level of 102 pg/ml at 4 hours 57 .…”
Section: E2 Delivery Using Plga Mncsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the approaches for exploiting nanotechnology developments in medicine, several nanoparticulates offer certain unique advantages as pharmaceutical delivery systems and image enhancement agents (West & Halas, 2000;LaVan et al, 2002). Varieties of nanoparticles (Sahoo & Labhasetwar, 2003) such as different polymeric and liposomes, metal nanoparticles, micelles, Mittal et al (2009) quantum dots, microcapsules, dendrimers, cells, cell ghosts, lipoproteins and many different nanoassemblies are available. All these nanoparticles can play a main role in diagnosis and therapy.…”
Section: Nanoparticle Carrier Systemmentioning
confidence: 99%